478. Lung Hybrid Neutrophils and Subsequent Extracellular Traps Are Protective In COVID-19-Associated Pulmonary Aspergillosis. (15th December 2022) - Feys, Simon; Vanmassenhove, Sam; Kraisin, Sirima; Cambier, Seppe; Jacobs, Cato; Boeckx, Bram; Mol, Pierre Van; Vanderbeke, Lore; Lagrou, Katrien; Weyenbergh, Johan Van; Carvalho, Agostinho; Veerdonk, Frank Van De; et al.
Abstract: Background: COVID-19-associated pulmonary aspergillosis (CAPA) is a severe superinfection with the fungus Aspergillus frequently affecting critically ill COVID-19 patients. Pathophysiological insight, key to improve diagnostic and immunomodulatory therapeutic options, is lacking. Methods: We performed single-cell RNA sequencing (scRNA-seq) on 37 bronchoalveolar lavage (BAL) samples from 37 critically ill COVID-19 patients. Three groups were defined: patients who did not develop aspergillosis (COVID-19-only, n=22), CAPA patients with sampling < 5 days after CAPA diagnosis (early CAPA, n=6) and CAPA patients with sampling 5-11 days after CAPA diagnosis (late CAPA, n=9). All CAPA patients had probable/proven CAPA according to the 2020 ECMM/ISHAM consensus criteria. Additionally, we assessed neutrophil extracellular trap (NET) levels in a separate cohort of 33 biobanked COVID-19-only BAL samples and 24 early CAPA samples. Results: A total of 69008 cells passed quality filtering. CAPA patients had significantly lower BAL neutrophil proportions than COVID-19-only patients, particularly in early CAPA (Fig. 1A). Pseudotime inference revealed two neutrophil trajectories: a regular maturation trajectory, and a trajectory giving rise to "hybrid" neutrophils which express genes encoding proteins with antigen-presenting functions (Fig. 1B). The latter trajectory was dominant in CAPA patients (Fig. 1C). NETosis analyses revealed significantly higher levels of citrullinated histone H3 DNA complexes (H3Cit-DNA) in CAPA patients (Fig. 2A). This explains the low CAPA BAL neutrophil proportions, as neutrophils that underwent NETosis are no longer detected via scRNA-seq. CAPA patients with the lowest H3Cit-DNA levels had significantly decreased survival rates (Fig. 2B). Figure 1: Bronchoalveolar lavage fluid (BALF) neutrophil proportions are significantly decreased in CAPA patients, accompanied by a shift to hybrid neutrophil formation. Panel (A): BALF neutrophil proportions as analyzed by single-cell RNA sequencing using the Seurat R package are significantly lower in CAPA patients compared to COVID-19-only patients. Patients with early CAPA have significantly lower BALF neutrophil proportions than patients with late CAPA. Macrophage/monocyte and epithelial cell proportions are reciprocally increased in CAPA patients compared to COVID-19-only patients. P-values shown for differences between the pooled CAPA patients and the COVID-19-only patients. P-values were calculated using a generalized linear model correcting for age, Charlson Comorbidity Index at hospital admission, and administration of corticosteroids (prednisone equivalent dose 20 mg or higher) within 48 hours of BALF sampling. Panel (B): Two trajectories are defined using pseudotime inference calculated using the Slingshot R package: a trajectory dominant in COVID-19-only patients with regular maturation of progenitor neutrophils, and a trajectory dominant in CAPA patients with maturation towards a 'hybrid neutrophil' state, with neutrophils expression genes encoding proteins with functions in antigen presentation. Subsequently, the hybrid neutrophil proportion is significantly higher in CAPA patients compared to COVID-19-only patients, and is significantly higher in patients with early CAPA than those with late CAPA. The mature neutrophil proportion is reciprocally reduced in CAPA patients. P-values shown for differences between the pooled CAPA patients and the COVID-19-only patients. P-values were calculated using a generalized linear model correcting for age, Charlson Comorbidity Index at hospital admission, and administration of corticosteroids (prednisone equivalent dose 20 mg or higher) within 48 hours of BALF sampling. Figure 2: Neutrophil extracellular trap (NET) levels are increased in early CAPA and are associated with increased survival in CAPA patients specifically. Panel (A): Myeloperoxidase (MPO) DNA levels were analyzed as measure for general NET-formation, while citrullinated histone H3 bound DNA (H3Cit-DNA) levels were analyzed as more specific PAD4-dependent NET-formation, in BALF samples from early CAPA and COVID-19-only patients. A trend towards higher MPO-DNA levels was found in early CAPA patients, while H3Cit-DNA levels were significantly higher in early CAPA compared to COVID-19-only patients. P-values calculated using Mann-Whitney U test. Panel (B): Kaplan-Meier analysis of patients with NETosis analyses, divided in early CAPA and COVID-19-only patients and subdivided according to H3Cit-DNA levels (cut-off at 20000 ng/mL for early CAPA and at 8000 ng/mL for COVID-19-only). Log-rank test was used to compare survival distributions. For the comparison early CAPA (low H3Cit-DNA) versus early CAPA (high H3Cit-DNA), the log-rank p-value was 0.033. Conclusion: CAPA patients display extremely high levels of released NETs in the lower respiratory tract, associated with a shift from the normal neutrophil maturation process towards "hybrid neutrophil" formation, probably upon encountering the fungus. In contrast to high NETosis contributing to mortality in severe COVID-19, CAPA patients likely require these NETs to survive aspergillosis. BAL NET levels hold promise as a tool to guide diagnosis, prognosis and treatment in these patients. Disclosures: Simon Feys, MD, Pfizer: Travel support Katrien Lagrou, PharmD, PhD, FUJIFILM Wako: Speaker fee|Gilead: Advisor/Consultant|Gilead: Speaker fee|MRM Health: Advisor/Consultant|MSD: Advisor/Consultant|Pfizer: Speaker fee|Thermo fisher Scientific: Service fee Joost Wauters, MD, PhD, Gilead: Grant/Research Support|Gilead: Speaker's fee, travel support, advisory board|MSD: Grant/Research Support|MSD: Speaker's fee, travel support, posaconazole for interventional trial|Pfizer: Grant/Research Support|Pfizer: Speaker's fee, travel support, advisory board.